Combined effects of dietary Laminaria digitata with alginate lyase on plasma metabolites and hepatic lipid, pigment and mineral composition of broilers - Costa, Mónica Mendes (2022)
Background: The Laminaria digitata is an abundant macroalga and a sustainable feedstock for poultry nutrition. L. digitata is a good source of essential amino acids, carbohydrates and vitamins, including A, D, E, and K, as well as triacylglycerols and minerals, in particular iron and calcium. However, the few studies available in the literature with broilers document the application of this macroalga as a dietary supplement rather than a feed ingredient. No study has addressed up until now the effects of a high-level incorporation (> 2% in the diet) of L. digitata on plasma biochemical markers and hepatic lipid composition, as well as minerals and pigments profile in the liver of broilers. Our experimental design included one hundred and twenty Ross 308 male birds contained in 40 wired-floor cages and distributed to the following diets at 22 days of age (n = 10) for 15 days: 1) a corn-soybean basal diet (Control); 2) the basal diet plus 15% of L. digitata (LA); 3) the basal diet plus 15% of L. digitata with 0.005% of Rovabio® Excel AP (LAR); and 4) the basal diet plus 15% of L. digitata with 0.01% of the recombinant CAZyme, alginate lyase (LAE). Results: L. digitata compromised birds’ growth performance by causing a reduction in final body weight. It was found an increase in hepatic n-3 and n-6 fatty acids, in particular C18:2n-6, C18:3n-6, C20:4n-6, C20:5n-3, C22:5n-3 and C22:6n-3 with the addition of the macroalga, with or without feed enzymes, to the broiler diets. Also, the beneficial C18:3n-3 fatty acid was increased by combining L. digitata and commercial Rovabio® Excel AP compared to the control diet. The sum of SFA, MUFA and the n-6/n-3 PUFA ratio were decreased by L. digitata, regardless the addition of exogenous enzymes. β-carotene was enhanced by L. digitata, individually or combined with CAZymes, being also responsible for a positive increase in total pigments. Macrominerals, in particular phosphorous and sulphur, were increased in the liver of broilers fed L. digitata individually relative to the control. For microminerals, copper, iron and the correspondent sum were consistently elevated in the liver of broilers fed L. digitata, individually or combined with exogenous CAZymes. The powerful discriminant analysis tool based on the hepatic characterization revealed a good separation between the control group and L. digitata diets but failed to discriminate the addition of feed enzymes